Pengaruh Lokasi, Potongan Harga Dan Kualitas Produk Terhadap Loyalitas Pelanggan Pada PT. SS Jaya Group Kota Kediri - Ella Fitriawati; Bambang Suwarsono; Brahma Wahyu Kurniawan (Master Manajemen, 2023)
This research discusses location, price discounts and product quality on customer loyalty at PT. SS Jaya Group Kediri City, this research aims to determine the results of the influence of location, price discounts and product quality on customer loyalty at PT SS Jaya Group Kediri City. The method in this research is the Quantitative Method. Data collection techniques use primary data and secondary data. Sampling in this study used purposive sampling technique with a sample size of 88 people. Data processing uses validity test, reliability test, classical assumption test, multiple linear regression test, coefficient of determination, F test, t test. There is a partial influence between Location on Customer Loyalty where the t test results obtained a significant value of 0.011<0.05. There is a partial influence between price discounts on customer loyalty where the t test results obtained a significant value of 0.000 < 0.05. There is a partial influence between Product Quality and Customer Loyalty where the t test results obtained a significant value of 0.007 < 0.05. There is a simultaneous influence of Location, Price Discounts and Product Quality on Customer Loyalty where the F test results obtained a significant value of 0.000<0.005.